National law on access to genetic resources and benefit- sharing: Impact on food security and traditional knowledge associated with genetic resources / Gurdial Singh Nijar - Gurdial Singh, Nijar (2017)
Food security for developing countries has been assured through the practice over millennia of farmers freely using and exchanging genetic resources for food and agriculture. Further, countries have been freely utilizing and exchanging such genetic resources. This establishes a high level of global inter-dependency for these resources. However, food security could well be threatened by international treaties such as the Convention on Biological Diversity and the Nagoya Protocol on Access and Benefit-sharing of Genetic Resources arising for their Utilization which provide for countries to enact national laws or policies to regulate access to these resources.